Respuesta :

Answer:

Graph #1

Step-by-step explanation:

Compare your

y - 1 = (2/3)(x - 3) to

y - k = m(x - h).  We see that k = 1 and h = 3.

Thus, (1, 3) is a point on the graph.  This matches Graph #1.  

Note: Graph #1 and Graph #3 appear to be the same.  Why?

Answer:

The graph of the equation is:

                          Graph 1

Step-by-step explanation:

The equation is given by:

    [tex]y-1=\dfrac{2}{3}\times (x-3)[/tex]

Now, we will see the point through which the graph passes through.

when x=3 we have:

[tex]y-1=\dfrac{2}{3}\times (3-3)\\\\i.e.\\\\y-1=\dfrac{2}{3}\times 0\\\\i.e.\\\\y-1=0\\\\i.e.\\\\y=1[/tex]

i.e. the graph passes through (3,1)

and also when x= -3 we have:

[tex]y-1=\dfrac{2}{3}\times (-3-3)\\\\i.e.\\\\y-1=\dfrac{2}{3}\times -6\\\\i.e.\\\\y-1=2\times -2\\\\i.e.\\\\y-1=-4\\\\i.e.\\\\y=-4+1\\\\i.e.\\\\y=-3[/tex]

i.e. the graph passes through (-3,-3)

The graph which satisfies these two points is: Graph 1

ACCESS MORE